Patho-anatomical studies on african swine fever in Uganda - Ganowiak, J. (Swedish University of Agricultural Sciences, 2012)
African Swine Fever (ASF) is one of the most serious transboundary swine diseases because of its high lethality for pigs, socioeconomic consequences, rapid and international spread and the absence of either treatment or vaccine. This Sida Minor Field Study (MFS) was carried out during fall 2010, as part of a larger collaborative research project called ASFUganda, focusing on the epidemiology of the disease in Uganda. The aim with this study was to get more knowledge about the pathology in cases of ASF in Uganda, by studying macroscopic and microscopic lesions in pigs with acute and chronic ASF and to detect the ASF virus (ASFV) in tissues by immunohistochemistry.The pigs were selected from the two different geographical locations in Uganda, Mityana and Gulu district, both with on going confirmed outbreaks of ASF. Necropsies were performed in the field, and the laboratory procedures at the JICA (Japan International Cooperation Agency) Veterinary Pathology Laboratory, Entebbe, Uganda, and at the Department of BVF, SLU, Uppsala, Sweden. Three pigs from an outbreak of ASF in Mityana district showed both the history and the clinical symptoms typical for ASF. The macroscopic and histopathological findings were consistent with the lesions described in the literature for acute ASF. ASFV antigen was detected by immunohistochemistry in the lymphoid tissues from these pigs, indicating that the lesions were the direct result of the virus infection. Three pigs from Gulu district did not show any clinical symptoms of ASF disease before slaughter but were positive for ASFV on RT-PCR and ELISA. The macroscopic and histopathological findings resembled the lesions previously described for subacute and chronic ASF.